Women Resistance Towards Men Domination And Race Discrimination In Freedom Writers (2007) - Vena Katrinada; Muhammad Thoyibi (Jurnal Educatio FKIP UNMA, 2023)
This research aimed at analyzing: 1) what are the indicators of women resistance, 2) how was women resistance illustrated in the movie, 3) why did Richard LaGravanese bring the issues of women resistance in the movie. The type of this study is qualitative. The data collection technique that be used by the researcher is documentation method. The data obtained are in the form of dialogues, pictures, and explanations of situations found in movie and transcript which show data showing forms of women's resistance to men domination and racial discrimination contained in the movie. The results show that the indicators of women resistance, namely: 1) fight for equality; 2) dare to make decisions; 3) can convey without hesitation their experience, which is also valuable; 4) can express an opinion and stick to it; 5) dare to take their rights and opportunities. There are five data that illustrate how the women resistance toward the domination and discrimination they receive. Last, this movie is interesting about how women can resist dominations and discriminations which can inspire many other women out there to have the courage to make decisions, to have determination, to have the courage to resist inequality.